Range GLS-Coding: A Scheme of Simultaneous Data Compression and Encryption (Journal of Informatics and Mathematical Sciences, 2016)
This paper presents an improved version of GLS-coding for simultaneous data compression and encryption called Range GLS-coding. It removes implementation issue of infinite precision real numbers due to long products of real numbers in GLS-Coding. This improvement increases the algorithm efficiency to almost double. Furthermore, encryption quality is improved by masking pseudorandom keystream; the secret key is incorporated by changing the direction and performing cyclic-shift operation in a complex piecewise linear chaotic map (PWLCM). Experimental results demonstrate that proposed algorithm has acceptable security and compression features. The overall algorithm provides simultaneous data encryption and compression and useful for real-time applications.
Keywords: GLS-Coding; compression; encryption; simultaneous compression and encryption